E-LEADERSHIP STRATEGY IN THE DEVELOPMENT OF SUSTAINABLE TOURISM IN RAJA AMPAT BASED ON GREEN TOURISM - Sinen, Karmila; Nurinaya, Nurinaya; Rahman, Guntur Abd (Jurnal Education and Development, 2026)
This study explores the role of E-Leadership in advancing sustainable tourism in Raja Ampat, one of Indonesia's leading marine tourism destinations. Raja Ampat is renowned for its extraordinary natural beauty, rich marine biodiversity, and vibrant local culture. However, the rapid growth of tourism in the region has raised environmental and socio-cultural challenges that require innovative and sustainable management approaches. The main issue addressed in this study is the lack of effective environmentally friendly tourism management and the suboptimal use of digital technology in destination governance. The aim of this research is to analyze how E-Leadership can be applied as a strategy to manage tourism sustainably in Raja Ampat. This study uses a descriptive qualitative approach, employing literature review and in-depth interviews with tourism stakeholders such as local governments, business actors, and community members. The results indicate that E-Leadership significantly contributes to enhancing transparency, strengthening stakeholder collaboration, and accelerating data-driven decision-making processes. By integrating the principles of green tourism and sustainable development, E-Leadership has proven effective in supporting the protection of natural resources, empowering local communities, and ensuring long-term economic resilience. This paper highlights how digital technology, when effectively implemented through E-Leadership, can facilitate responsible tourism practices and contribute to the preservation of Raja Ampat's ecological and cultural heritage.